2015
DOI: 10.1146/annurev-astro-082812-140951
|View full text |Cite
|
Sign up to set email alerts
|

Physical Models of Galaxy Formation in a Cosmological Framework

Abstract: Modeling galaxy formation in a cosmological context presents one of the greatest challenges in astrophysics today, due to the vast range of scales and numerous physical processes involved. Here we review the current status of models that employ two leading techniques to simulate the physics of galaxy formation: semi-analytic models and numerical hydrodynamic simulations. We focus on a set of observational targets that describe the evolution of the global and structural properties of galaxies from roughly Cosmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
1,093
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 1,349 publications
(1,138 citation statements)
references
References 551 publications
20
1,093
0
3
Order By: Relevance
“…The rate at which this gas can cool is determined by a simple spherical cooling flow model (see Somerville et al (2008) for details) which approximates the transition from "cold flows", where cold gas streams into the halo along dense filaments without being heated, to "hot flows", where gas is shock heated on its way in, forming a diffuse hot gas halo before cooling (Birnboim & Dekel 2003;Kereš et al 2005;Dekel & Birnboim 2006). In this way, virial shock heating is included in our SAM, although many studies show that this effect alone is not enough to produce the observed population of massive quiescent galaxies (Somerville & Davé 2015, and references therein).…”
Section: The Semi-analytic Modelmentioning
confidence: 99%
“…The rate at which this gas can cool is determined by a simple spherical cooling flow model (see Somerville et al (2008) for details) which approximates the transition from "cold flows", where cold gas streams into the halo along dense filaments without being heated, to "hot flows", where gas is shock heated on its way in, forming a diffuse hot gas halo before cooling (Birnboim & Dekel 2003;Kereš et al 2005;Dekel & Birnboim 2006). In this way, virial shock heating is included in our SAM, although many studies show that this effect alone is not enough to produce the observed population of massive quiescent galaxies (Somerville & Davé 2015, and references therein).…”
Section: The Semi-analytic Modelmentioning
confidence: 99%
“…Observationally, satellites in general depend on both intrinsic and environmental parameters for their quenching, whereas centrals depend primarily only on intrinsic properties (e.g., Peng et al 2012). In many simulations and models, the quenching of central galaxies is governed primarily by AGN feedback and the quenching of satellite galaxies is governed primarily by environmental processes, such as, e.g., strangulation or stripping (e.g., Guo et al 2011;Vogelsberger et al 2014a,b;Henriques et al 2015;Schaye et al 2015;Peng et al 2015;Somerville et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There, it condenses into neutral and then molecular gas, some of which is then converted into stars. Young stars, in turn, drive strong winds, outflows, and radiation that deposit mass, metals, energy, and momentum to the CGM, thus significantly influencing its properties (see review by Somerville & Davé 2015;Fielding et al 2016, and references therein). These linked processes are commonly termed the baryon cycle.…”
Section: Introductionmentioning
confidence: 99%